(untitled) (Journal of Faculty of Education, 2022)
Eight species of commercial Nile fish were studied to determine the protein, secondary protein, lead amount and moisture content. The study employed ordinary laboratory equipments together with Fourier Transformation Infrared (FTIR) and Atomic Absorption Spectroscopy (AAS). The results obtained showed that the protein content was in the range 19.7 to 51.3 %, lead amount in the range of 0.08 to 0.8 ppm, and the moisture content 16.3 to 24.5 %. The structures showed that the eight samples of α-helix, β- parallel, β- antiparallel and unordered forms all exist in the Nile fish. It is concluded that the Nile fish is good nutritive, in a safe aquatic biota. شملت الدراسة ثماني عينات من أسماك النيل لتحديد محتوى البروتين ، البروتين الثانوي، الرصاص و محتوى الرطوبة. إن هيكلة البروتين و كمياته مهمة للغذاء كما امتدت الدراسة لتشمل توقع المخاطر التي تنتج من السلاسل المتراكبة لتنظيم البروتين و التي تختص بالمشكلات الصحية للإنسان و الحيوان و الدواجن .استخدمت الدراسة الأجهزة المختبرية الزجاجية كما استخدمت تقنية جهاز الأشعة تحت الحمراء على نظام فورير و جهاز المطيافية الإمتصاصية الذرية. و قد توصلت الدراسة للنتائج التالية: المحتوى البروتيني للعينات في المدى 19.7– 51.3%، الرصاص في المدى0.08 - 0.8 جزء من المليون ( و هو نسبة صغيرة جداً لا تكاد تذكر) و محتوى الرطوبة16.3– 24.5% . أثبتت الدراسة أن العينات بها حلزون ألفا و متوازي بيتا و متوازي عكسي بيتا و النوع غير المنتظم و أن الأسماك النيلية هذه جيدة للغذاء و في بيئة مائية إحيائية آمنة